Instructional Facilities in Secondary Level School of Banke District, Nepal - Acharya, Lal Mani; Maharjan, Ram Krishna (Journal of Advanced Academic Research, 2018)
Talking about the instructional facilities indicates the facilities available for the classroom teaching and learning of students. This is the age of modern technology so students want to learn with new tools and techniques. In this context, school should be aware on the management of such basic facilities in school. The aim of this study is to identify the instructional facilities in secondary level school of Banke district of Nepal. The study was based on the descriptive and exploratory research design. In total 674 students from public and private secondary schools were selected for the study. Structure questionnaire survey was done to collect the data. The result shows that comparatively, the instructional facilities were better in private school than the public school. Private school had managed the computer aided teaching system, separate computer and science lab better than the public school. Considering the better result in final exam, private school has managed the additional coaching class for their students than the public school. Public schools are service oriented supported by Nepal Government so government should be responsible to improve the quality of teaching, learning and infrastructure development as the demand of modern teaching system.